Pandemic (H1N1) 2009 outbreak on pig farm, Argentina - Pereda, Ariel (2010)
In June-July 2009, an outbreak of pandemic (H1N1) 2009 infection occurred on a pig farm in Argentina. Molecular analysis indicated that the virus was genetically related to the pandemic (H1N1) 2009 influenza virus strain. The outbreak presumably resulted from direct human-to-pig transmission.